Sirolimus Use in Liver Transplant Recipients With Hepatocellular Carcinoma: A Randomized, Multicenter, Open-Label Phase 3 Trial. Issue 1 (January 2016) - Geissler, Edward K.; Schnitzbauer, Andreas A.; Zülke, Carl; Lamby, Philipp E.; Proneth, Andrea; Duvoux, Christophe; Burra, Patrizia; Jauch, Karl-Walter; Rentsch, Markus; Ganten, Tom M.; Schmidt, Jan; Settmacher, Utz; et al.
Abstract : Background: We investigated whether sirolimus-based immunosuppression improves outcomes in liver transplantation (LTx) candidates with hepatocellular carcinoma (HCC). Methods: In a prospective-randomized open-label international trial, 525 LTx recipients with HCC initially receiving mammalian target of rapamycin inhibitor–free immunosuppression were randomized 4 to 6 weeks after transplantation into a group on mammalian target of rapamycin inhibitor–free immunosuppression (group A: 264 patients) or a group incorporating sirolimus (group B: 261). The primary endpoint was recurrence-free survival (RFS); intention-to-treat (ITT) analysis was conducted after 8 years. Overall survival (OS) was a secondary endpoint. Results: Recurrence-free survival was 64.5% in group A and 70.2% in group B at study end, this difference was not significant ( P = 0.28; hazard ratio [HR], 0.84; 95% confidence interval [95% CI], 0.62; 1.15). In a planned analysis of RFS rates at yearly intervals, group B showed better outcomes 3 years after transplantation (HR, 0.7; 95% CI, 0.48-1.00). Similarly, OS ( P = 0.21; HR, 0.81; 95% CI, 0.58-1.13) was not statistically better in group B at study end, but yearly analyses showed improvement out to 5 years (HR, 0.7; 95% CI, 0.49-1.00). Interestingly, subgroup (Milan Criteria-based) analyses revealed that low-risk, rather than high-risk, patients benefited most from sirolimus; furthermore, younger recipients (age ⩽60) also benefited, as well sirolimus monotherapy patients. Serious adverse event numbers were alike in groups A (860) and B (874). Conclusions: Sirolimus in LTx recipients with HCC does not improve long-term RFS beyond 5 years. However, a RFS and OS benefit is evident in the first 3 to 5 years, especially in low-risk patients. This trial provides the first high-level evidence base for selecting immunosuppression in LTx recipients with HCC. Abstract : In a large prospective randomized open-label international trial, liver transplant recipients for HCC were randomized to receive non-mTOR-inhibitor-based-treatment or mTOR-inhibitor-based-treatment. Results indicate overall sirolimus does not improve long-term recurrence-free survival beyond 5 years while a benefit was seen in low-risk patients. Supplemental digital content is available in the text.